Why do countries engage in the preferential trade agreement network? - Flavia Rovira; Marcel Vaillant (Revista de Economía y Estadística)
We analyze the determinants of Preferential Trade Agreements Networks dynamics. We propose a theoretical framework based in an extension of Baldwin (1995) to rationalize the determinants of PTA formation as a way to maximize preferential market access and/or diminish market discrimination. To build the empirical model we use a Stochastic Actor Oriented Models proposed by Snijders (2001). We suppose that three main set of variables will affect the countries motivation to change their PTA neighborhood at each moment. The first is related to natural trade cost and market size. The second group is related to political economy effects. And finally, we include a variable related to trade specialization, which has not been used in earlier works to explain PTAs. Following Snijders et al. (2012) we also control for hierarchy structures of the PTA, and we extend their work by analyzing the change in this phenomenon when considering a broader period of time. Results show that the signs of usual variables behave as expected in the literature for the first period but hierarchy effect dilutes after 2004. As a contribution to existing literature, we found that trade rivalry between countries is also significant in explaining the dynamics of PTA.